Perioperative blood loss evaluation in tumour-related limb salvage pelvic resections - Sharifudin, Mohd Ariff; Wan, Zulmi; Wan Ismail, Wan Faisham Numan; Mat Zin, Nor Azman; Mohamed Amin, Mohamed Azril; Goh, Kian Liang (2014)
Introduction and Objectives: Pelvic tumour resections are associated with extensive blood loss. Various options of blood management in surgery are available but limited use particularly for such procedures. Identifying predictive factors for extensive blood loss is essential. This study aims to evaluate the volume of blood loss in limb salvage pelvic resections and identify the risk factors for large amount of perioperative blood loss. Methodology: Twenty-five cases of pelvic tumours of various types, whom underwent resections performed between year 2000 and 2010 in a single tumour referral centre were reviewed. External hemipelvectomies and sacral resections were not included. Total perioperative blood loss consisted of estimated intra-operative blood loss and the drainage volume on the first day post-surgery. Large amount of blood loss was defined as total loss of more than 3000ml. Statistical analysis performed using Fisher’s exact test. Results: Six (24.0%) patients had total blood loss greater than 3000ml. Resections of primary bone sarcomas (osteosarcoma and chondrosarcoma) have the highest mean blood loss volume (6556.67ml and 1768.57ml, respectively). Large amount of blood loss is significantly associated with the involvement of the acetabulum. Other associated factors include tumour recurrence and duration of surgery. Extensive blood loss was not significantly associated with neo-adjuvant therapies and pre-operative embolization. Conclusion: Large amount of blood loss should be anticipated when planning for resections of tumours involving the acetabular region. Radiation therapy prior to surgery was believed to increase the risk of bleeding intra-operatively, was not observed in this study.